Gulf alliances : regional states hedge their bets - James M. Dorsey (2015)
The Saudi-led intervention in Yemen designed to prevent Iranian-backed forces from gaining power symbolises the Gulf’s new assertiveness. Potential US-Iranian agreement on resolving the nuclear crisis has fuelled concern among Arab Gulf states about the reliability of the United States as the region’s ultimate security guarantor.